Постановка проблеми та напрями дослідження правової традиції: логіко-методологічний аналіз - Лобода, Ю.П. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассматриваются основные направления в исследовании правовой традиции с позиций логико-методологического анализа. Автор приходит к заключению, что, характеризуя сущность современной правовой системы Украины, необходимо учитывать особенности последней в процессе её взаимодействия с европейским пространством в контексте европейской правовой культуры. The article figures out the main ways of law tradition investigation from the logical and methodolocical point of view. The author makes his own conclusions towards the process of investigation: while building the characteristics of the modern ukranian law system being, one should consider its special features in the context of the interrelations with europenian culure.